Calidad del servicio y satisfacción de los clientes de la clínica Prontto Salud Trujillo 2017 - Arroyo Villar, Juan Daniel (2018)
The present research work has been carried out in order to determine the influence of the quality of service on the satisfaction of the clients of the Clinic Prontto, Trujillo 2017. The problem formulated for the investigation was: What is the relationship that exists between the quality of the service and the satisfaction of the clients of the Prontto Salud Clinic, Trujillo 2017? And it was hypothesized: There is a direct relationship between the quality of the service and the satisfaction of the clients of Clínica Prontto Salud, Trujillo, 2017. The population under study was made up of monthly users and / or patients who attend the different services provided by the Prontto Salud Clinic. It was considered, according to data of the company, a monthly average of 2450 users and / or patients, having as sample to 332 users. The research design used was descriptive-transversal and the methods were: inductive, statistical, analytical and synthetic. Regarding the technique, the survey was used and the questionnaire was used as instruments. It was obtained as a result that the users perceive the quality of the service in general as a service of the average quality and the level of satisfaction of the same ones is in a high average level. In addition, we can highlight that the most important attributes of the service for the users turned out to be trust, reliability, and security. These results were the basis for recommending actions to improve customer satisfaction. Likewise, the conclusion reached was that the quality of the service has a direct influence on customer satisfaction. Improving the quality of the service will result in an increase in the satisfaction of the clients of Clínica Prontto Salud, Trujillo, 2017.